Physicochemical and environmental plant physiology - Nobel, Park S. (London, United Kingdom Academic Press, an imprint of Elsevier., 2020)
"Physicochemical and Environmental Plant Physiology, Fifth Edition, is the updated version of an established and successful text and reference for plant scientists. This work represents the seventh book in a 50-year series by Park Nobel beginning in 1970. The original structure and philosophy of the book continue in this new edition, providing a genuine synthesis of modern physicochemical and physiological thinking, while updating the content. Key concepts in plant physiology are developed with the use of chemistry, physics, and mathematics fundamentals"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Plant physiology; Botanical chemistry; Plant ecophysiology; Plant cells and tissues